ECRANIZATION ANALYSIS OF THE NOVEL INTO THE MOVIE “ALLEGIANT” BY VERONICA ROTH - anisa ulkhusnah (Journal Albion : Journal of English Literature, Language, and Culture, 2023)
This research was entitled "Analysis of Novel Ecranization Into the Film "Allegiant" by Veronica Roth". This study tried to discuss ecranization of novels into movies. This study is to review the intrinsic elements in Allegiant's novel, especially the setting, characters, plot, and style that underwent reduction, addition and modification in the film. This study conducted as a qualitative research. This study used descriptive method by analyzing novels and films. From this analysis the researcher found as well as a comparison of the changes in the ecranization of the Allegiant film novel namely 12 reductions, 5 additions, and 8 modifications. The characters in the reduction are 6 RDN, there are 2 RDN styles, 2 RDN plots then 2 RDN settings. In addition, there was 1 ADN in the setting and 4 ADN in the plot. Furthermore, in the modification, the researcher found 4 MDN in the setting, 1 MDN in character, and 3 MDN in the plot.